The interaction among the regulation of New Plant Breeding Techniques, GMO labeling, and coexistence and segregation costs: The case of rapeseed in the EU - Thomas J. Venus; Dušan Drabik; Justus Wesseler (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2017)
We analyze the market and welfare effects of regulating crops derived by New Plant Breeding Techniques (NPBTs) as genetically modified (GM) or conventional products. We consider the EU mandatory scheme for labeling GM products and a voluntary non-GM scheme for labeling livestock products derived from non-GM feed. We develop a partial equilbrium model that explicitly takes into account both the coexistence costs at farm-level and the segregation and identity preservation costs at downstream level. By applying the model to EU rapeseed, we find that regulating NPBTs as GM (as compared to non-GM) in combination with mandatory and voluntary labeling increases prices and makes consumers overall worse off and producers better off. We also show that higher coexistence costs make the price increasing effect even stronger. Voluntary non-GM labeling applied to feed makes consumers in this sector overall worse off but benefits farmers and rapeseed oil consumers overall as long as segregation costs are low. Consumers of biodiesel and industrial products such as lubricants produced from GM rapeseed benefit from high segregation costs. We show that the effects of farm-level coexistence costs largely differ from the effects of downstream market segregation costs.
Keywords: Q18; 330; New Plant Breeding Techniques; GMO; labeling; coexistence; identity preservation; regulation; vertical product differentiation